CLINICAL AND SUBCLINICAL CHARACTERISTICS IN CHILDREN BELOW 1 YEAR OLD HAVE BEEN FULL SURGERY TO TREAT TETRALOGY OF FALLOT (Vietnam Journal of Community Medicine, 2022)
Objective: Review of clinical, subclinical and surgical results of total repair of tetralogy of Fallot inchildren under 1 year old at Hanoi Heart Hospital and Thanh Hoa Children’s Hospital.Methods: A cross-sectional descriptive study on 115 patients at Thanh Hoa Children’s Hospital andHanoi Heart Hospital in 2016.Results: Pediatric patients have typical clinical symptoms such as slow weight gain (73%), syncope(7.8%), dyspnoea (20%), cyanosis (40%), and cyanosis of different levels (84, 5). 3%), systolicmurmur (100%), SpO2 less than 80% (21.7%). The patient had an increase in erythrocyte index(14.8%) and hematocrit (0.9%). On the X-ray film, the lungs are bright (48.7%), and the heart isconcentric (26.1%). The results of the electrocardiogram showed that the proportion of patients withright ventricular hypertrophy was 39.1%. The proportion of patients with right bundle branch blockaccounts for 13%. Echocardiographic results showed that the majority of patients had 1 ventricularseptal defect (98.3%). Most of the pediatric patients had stoma in the peri-membrane position(98.3%). The mean right ventricular–pulmonary difference was 83.7±20.8 mmHg (40 – 153 mmHg).The proportion of patients with a gradient over 75 mmHg is 60%. The mean left ventricular function(EF) was 68.8±6.9% (54-85%); The mean right ventricular dilatation index was 0.6±0.1 (0.4–1.1)and the mean right ventricular funnel diameter was 4.2±1.3 mm (2-7mm).Conclusion: Children under 1 year of age with tetralogy of Fallot who were indicated for total repairsurgery in the study had clinical and subclinical characteristics similar to those of older children, withcharacteristics of patients with tetralogy of Fallot.
Keywords: Tetralogy of Fallot, complete correction of tetralogy of Fallot, children under 1 year of age, children, clinical and subclinical characteristics.